Intersectionality in the access to justice for women victims of violence - Oviedo, Carolina (2022)
To approach the gaps in the access to justice derived from the intersectional discrimination against women is essential for the construction of the citizenry and the strengthening of the State governed by the Rule of Law. The exercise in full of the right to a life free of violence in the domestic and intra-family sphere requires rethinking these gaps from an intersectional standpoint. In this context, the case law adopted by the Inter American Court of Human Rights, by including the application of the Inter American Convention to prevent, sanction and eradicate violence against women, for the murder of a trans woman is the course we must take to build fairer societies. Societies that are not blind to the experiences of different and plural women in their search for justice.